Risk Factor Profile of Children With Cerebral Palsy at Sambang Lihum Psychiatric Hospital - Adelia Hanny Tiara; Wahyu Bagus Handoko; Bambang Dwiputranto; Haerati Haerati; Ramadiana Ramadiana (Medicinus, 2026)
Background: Cerebral palsy is a common childhood motor disorder caused by non-progressive disturbances in the developing brain. Local descriptions of risk factors are needed to support prevention, early detection, and rehabilitation planning. Methods: This descriptive cross-sectional study was conducted at Sambang Lihum Psychiatric Hospital from 1-31 March 2025. Fourteen children with cerebral palsy who underwent therapy or care during the study period were included. Data were obtained from medical records and parent or guardian interviews using a structured questionnaire and were analyzed descriptively. Result: Most children were aged 1-5 years (8/14; 57.2%). Maternal age during pregnancy was mostly 18-35 years (10/14; 71.4%). Nine children (64.3%) were born at <=37 weeks of gestation, and six (42.9%) had birth weight <2500 g. Most children had no history of head trauma (78.6%), febrile seizure (57.1%), or brain infection (92.9%). Conclusions: The most prominent risk factors identified in this sample were prematurity and low birth weight. Strengthening antenatal monitoring, neonatal care, and early rehabilitation remains important for children at risk of cerebral palsy.